(3QSGdI aj Jecjf GdeO aj Bef hBJi hBOe hChJi hTHggs - (3nepqcj Hf CHj WGdH nMoqehT Hf eMeO Hf eNJGQ GdCfOdSj GdbjSj, CHh eMeO,J (B437 (3g` s ((3CHhGdhaG Ydj Hf EHQGgje Hf YeQ Hf GdUGHhfj s)
(3ChdgG (B:s
(3SCdJ faYfG Gddg hEjGc Yf Jecjf GdeO aj Bef hBJi hBhJi hTHgg hPcQJ Cf bhekG GYJQVhG Ydi GdWdHg s
(3BNQgG (B:s
(3abO fUMJc Ef ZadJ YUefG Gddg JYGdi ef MejI GdLgd hJLGhR GdMb hGdZdh aj GdHGWd Efg Ydi Pdc bOjQ Je HMeO Gddg hYhfg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B94 (3H (B- (3U(B105 (3Cs
(3GdfSNI HgG MhGTs
(3YdjgG eWGdYI jQLY JGQjNgG SfI (B1087 (3g`s
(3fSNI ecQQI CjVkG JMJ Qbe (B36 (3bQGAGJ hJLhjO s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs